â€œSeafood not Slavefoodâ€: Advokasi Aktivisme Transnasional untuk Mengakhiri Praktik Perbudakan Modern di Industri Perikanan Thailand - Maziyah, Roihanatul; Susiatiningsih, Rr. Hermini (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2020)
In 2013, EJF (Environmental Justice Foundation) launched a global campaign named